تأثير الأزمة الراهنة على الصادرات الزراعية السورية - يعقوب, غسان; صقر, إبراهيم; مهنا, مجد (Latakia University Journal -Biological Sciences Series, 2017)
يهدف البحث إلى دراسة أهم مؤشرات الكفاءة الاقتصادية للتجارة الخارجية الزراعية، والتعرف على أهم المشكلات التصديرية التي تواجه الشركات والهيئات العاملة في مجال التجارة الزراعية الخارجية، وذلك باستخدام المنهج الوصفي التحليلي في معالجة المعطيات البحثية. فقد بينت النتائج أن معدل النمو السنوي للصادرات السورية خلال الفترة 2005 وحتى العام الأول من الأزمة 2011 بلغ نحو 15%، ومن عام 2005 وحتى نهاية عام 2014 نحو1%.كما أن القوة التصديرية الأعلى كانت من نصيب الكمون(56%) ، تليه البندورة (53%)، ثم التفاح( 26%)، ثم الدراق والعدس( 24%)، بينما انعدمت القوة التصديرية للأغنام، ولبعض المنتجات كالقمح والشعير والحمص والذرة.وقد توصلت نتائج البحث إلى وجود بعض المشكلات والعقبات التي تواجه الشركات العاملة، منها عدم دقة المعلومات التسويقية، خاصة عن الأسواق الخارجية، وعدم توافر الكميات المطلوبة للتصدير بالمواصفات المطلوبة، أو توافر العمالة المدربة على عمليات ما بعد الحصاد، بالإضافة إلى عراقيل بعض الأجهزة الوزارية الصحة والجمارك والضرائب... وغيرها. The research aims to study the most important economic efficiency of agricultural foreign trade indicators, and to identify the most important problems facing the export companies and organizations working in the field of foreign agricultural trade, using descriptive and analytical approach in the treatment of research data. The results show that the annual growth rate of Syrian exports during the period 2005 to the first year of the crisis in 2011 amounted to about 15%, and from 2005 until the end of 2014 about 1%. The export strength top of the share of latency (56%), followed by tomatoes (53%), and apples (26%), then peaches and lentils (24%), while zero, export strength of the sheep, but some products such as wheat, barley, chickpeas and corn.Search results have been reached and there are some problems and obstacles faced by the operating companies, including the lack of accurate marketing information especially for foreign markets, and the non-availability of required quantities for export to the required specifications, or the availability of skilled labor on the post-harvest operations, in addition to dent some of the ministerial organs, Health and customs and taxes ... and others.